2008
DOI: 10.2514/1.37395
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an Electromagnetic Mitigation Scheme for Reentry Telemetry Through Plasma

Abstract: During hypersonic reentry flight, the shock heated air generates a weakly ionized plasma layer. Because the weakly ionized plasma layer has a high plasma number density, it causes an important systems operation problem that is known as a communication, or radio, blackout. The radio blackout occurs when the plasma frequency of the plasma layer is higher than a radio wave frequency. In this case, the radio wave signals to and from the vehicle are reflected or attenuated so that the vehicle loses voice communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 17 publications
0
77
0
Order By: Relevance
“…For example, signal recoveries of very high frequency (VHF) telemetry and a Cband beacon with water injection as an electrophilic substance were observed in the Gemini 3 mission [2]. Kim et al [3] reported that plasma density can be controlled and RF blackouts can be reduced by applying a magnetic field on an antenna. In addition, Kundrapu et al [4] and Usui [5] numerically investigated the possibility of communication during an RF blackout via whistler mode.…”
Section: Introductionmentioning
confidence: 99%
“…For example, signal recoveries of very high frequency (VHF) telemetry and a Cband beacon with water injection as an electrophilic substance were observed in the Gemini 3 mission [2]. Kim et al [3] reported that plasma density can be controlled and RF blackouts can be reduced by applying a magnetic field on an antenna. In addition, Kundrapu et al [4] and Usui [5] numerically investigated the possibility of communication during an RF blackout via whistler mode.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation of electromagnetic waves through a plasma causes phenomena such as the radio-communication cut-off during spacecraft atmospheric re-entry 6,7 and the attenuation of signals through plasma plumes of modern electric propulsion systems; 8 and it is also used for the sustainment of plasma columns by surface wave 9 and the plasma diagnostics (microwave interferometry). 10 The phenomena of wave absorption/reflection via plasma occur when high-frequency (radiofrequency RF 1-300 MHz and microwaves MW>300 MHz) electromagnetic waves propagate in partially ionized plasmas.…”
Section: -3mentioning
confidence: 99%
“…This phenomenon is used in various applications, including plasma density diagnostic. It presents, however, a major problem for radio communications through dense plasmas which is created around a vehicle at re-entry, or during hypersonic flight [7][8][9][10]. Characterization of reflected and absorbed electromagnetic radiation is also of great interest for radar applications [11][12][13].…”
Section: Introductionmentioning
confidence: 99%